Epidemiology of typhoid fever in Gombe metropolitan area of Gombe State, Nigeria - Tawfiq, Umar Abdullahi (2021)
Typhoid fever is a human-restricted acute systemic and life-threatening disease which is caused by ingesting food or water contaminated with Salmonella typhi. This disease affects all genders and all ages but is more prevalent in developing countries especially those of Africa and Asia. Invasive Salmonella infections are responsible for a significant burden of morbidity and mortality with incidences of between 11 to 21 million infections and 128,000 to 161,000 mortalities globally, with 7.2million cases annually in Africa alone. In Nigeria, proper epidemiological data regarding typhoid fever is scanty and unavailable in most of the States like Gombe where the disease has been occurring for a long time without hinderance. In Gombe, typhoid fever occurrence is believed to be aggravated by absence of epidemiological data for health policy decisions and design of health interventions, lack of constant access to safe drinking water, poor hygiene, and inefficiency of environmental sanitation efforts. Thus, the research questions here include: Is there a significant association between host-associated risk factors and the occurrence/recurrence of typhoid fever in Gombe metropolis? And Is there a significant association between weather conditions and the incidence of typhoid in Gombe metropolis? Hence the aim of the research was the epidemiology of typhoid in Gombe metropolitan area of Gombe State, while the specific objectives included determination of incidence and recurrence, hostassociated risk factors, effect of weather on incidence, and overall counts of typhoid occurrences based on gender, age, and location. Incidence from 2015 to 2019 and recurrence for 2019 were determined using incidence proportions which were calculated from hospital records. A questionnaire was designed, validated, and used to obtain data for determining host-associated risk factors. Simple random sampling was used to collect information from 663 consenting respondents and the obtained data were analysed using Chi-square test for association and binomial logistic regression to obtain risk factors for typhoid occurrence and recurrence, respectively. Weather data from 2015 to 2019 were obtained from Nigeria meteorological agency, fitted to the hospital data, and analysed using Poisson regression to determine their effects on the incidence of the disease. Sum of counts were extracted from the hospital records based on gender, age, and location. Results from the study revealed that both typhoid incidence and recurrence were high in the study area because the number of cases were all greater than 100 per 100,000 persons per year for all the years included in the study. The questionnaire was easy to read and understand based on the Flesch reading ease score of 70.8 and Flesch-Kincaid grade level test value of 6.0, had good content validity based on the overall Fleiss’ (Multi rater) kappa value of 0.623, had good construct validity and internal consistency based on Cronbach’s alpha and McDonald’s omega values of 0.720 and 0.703 respectively, and had good test-retest reliability based on ICC value of 0.736 (99% CI = 0.533 to 0.878). Typhoid incidence was significantly associated with the variables for vaccination (χ2 = 39.729, p < 0.01), house help (χ2 = 16.909, p < 0.01), typhoid patient at home (χ2 = 13.393, p < 0.01), hand washing before handling food (χ2 = 22.856, p < 0.01), consuming iced/frozen items (χ2 = 16.805, p < 0.01), boiling drinking water (χ2 = 49.633, p < 0.01), and eating commercial foods/drinks (χ2 = 27.864, p < 0.01). Typhoid recurrence was significantly predicted by not sure of been vaccinated (OR = 2.962, CI = 1.290 to 6.802, p < 0.01), not having another typhoid patient at home (OR = 1.799, CI = 0.998 to 3.244, p < 0.01), and drinking unboiled water sometimes (OR = 2.130, CI = 1.023 to 4.434, p < 0.01). Increases in typhoid cases were also significantly predicted by increase of 1°C in minimum temperature (OR = 1.080, CI = 1.048 to 1.114, p < 0.01) and increase of 5% in humidity (OR = 1.041, CI = 1.031 to 1.051, p < 0.01). Females, individuals aged 21 to 30, and more populated areas, had the highest occurrences of the disease. At the end of this study, it was established that the designed/validated questionnaire is easy to read and understand, has moderate reliability, and good validity, hence can be used for collecting data to identify typhoid risk factors in the study area. It was also discovered that increase in typhoid incidences are related to elevations in temperature and humidity, and to some host-associated factors. It is thus believed that these findings will be invaluable to identification of populations at high risk of the disease, design of fitting prevention/control efforts, and guiding Government’s decisions on resource prioritization and efficient allocation of funds for prevention and control efforts against the disease.